Tingkat Kecemasan Pasien yang Menjalani Operasi di Rumah Sakit Panti Rapih Yogyakarta - Anggit Septy Nugraheni; Siwi Ikaristi Maria Theresia (I Care Jurnal Keperawatan STIKes Panti Rapih, 2020)
Background: Anxiety is often associated with a life-threatening event such as during surgery. The emergence of anxiety begins in the preoperative phase as the initial phase in the surgical process. For someone who is undergoing surgery for the first time, an anxious response will emerge so that it can affect the success of the operation. Objective: The purpose of this study was to determine the level of anxiety of patients who underwent the first operation at RapihPanti Hospital Yogyakarta. Methods: This research uses descriptive quantitative survey method, with a total sample of 30 respondents using purposive sampling technique. The instrument to assess used was the Hamilton Rating Scale for Anxiety (HRS-A) which was translated into Indonesian. Results: The results showed that the mild anxiety level was in the early elderly 16.7%. The most moderate level of anxiety in the elderly was 13.3% and severe anxiety in late adolescence was 3.3%. Based on gender, the level of mild anxiety was mostly experienced by men 33.3% and moderate anxiety was mostly experienced by women 30%. As many as 60% of patients get information sources on surgery from health workers and seek information on social media independently. Conclusion: The level of anxiety is mild, moderate and severe experienced by all age groups. Types of gender men experience the mild anxiety level and women experience the most moderate level of anxiety. Recommendation for nurses is to provide assistance in knowledge, understanding, and spiritual support, besides the nurses assess the level of anxiety in all patients undergoing surgery. For hospitals develop social media communication as a source of information on surgery.